Applications of Medical Physics - Gallo, Salvatore; Veronese, Ivan (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Applications of Medical Physics" is a Special Issue of Applied Sciences that has collected original research manuscripts describing cutting-edge physics developments in medicine and their translational applications. Reviews providing updates on the latest progresses in this field are also included. The collection includes a total of 20 contributions by authors from 9 different countries, which cover several areas of medical physics, spanning from radiation therapy, nuclear medicine, radiology, dosimetry, radiation protection, and radiobiology.